2023
DOI: 10.26441/rc22.1-2023-3034
|View full text |Cite
|
Sign up to set email alerts
|

Competencias profesionales en perfiles digitales: especialistas en posicionamiento web

Abstract: La mejora de la empleabilidad es uno de los objetivos clave de las Universidades, para lo cual es imprescindible identificar las competencias de los perfiles profesionales surgidos en la era digital, como el especialista en posicionamiento web o SEO (Search Engine Optimizer). Este artículo realiza una propuesta de perfil competencial y compara el grado de importancia otorgado por empresas y profesionales de un conjunto de competencias previamente identificado. Se ha seguido un diseño exploratorio secuencial (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
2
1
1
Order By: Relevance
“…In other times, these two skills were valued and required for important positions in an organization. This does not agree with what was reported by Escandell-Poveda et al (2023) who found that the least requested skills in organizations were communication skills and teamwork.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In other times, these two skills were valued and required for important positions in an organization. This does not agree with what was reported by Escandell-Poveda et al (2023) who found that the least requested skills in organizations were communication skills and teamwork.…”
Section: Discussioncontrasting
confidence: 99%
“…In the research work presented by Piñeiro he development of skills related to empathy, such as communication in teamwork, assertiveness, among others, are highlighted. Finally, the research of Escandell-Poveda et al (2023) indicate that the least requested skills in companies are communication skills and teamwork. In addition, the results showed a greater presence of men for jobs in the digital field.…”
Section: Introductionmentioning
confidence: 98%
“…Además, debe asegurar un conocimiento que fortalezca su desarrollo profesional en los ámbitos de innovación, tecnología, emprendimiento y gestión. Igualmente, debe considerar al entorno dinámico, por lo que requiere estar capacitado de acuerdo a las necesidades de la sociedad para aplicar las estrategias adecuadas que satisfagan tales exigencias (Escandell-Poveda, 2023).…”
Section: Aspectos Gerenciales En La Práctica Odontológicaunclassified
“…To achieve this objective, it is imperative to understand the skills demanded by the labor market (Pizarro-Lucas et al, 2021). Consequently, research efforts have been devoted to identifying the professional competencies required in various digital professions, such as search engine optimizers (Escandell-Poveda et al, 2023aor Escandell-Poveda et al, 2023b and community managers (Clemente-Mediavilla & Antolín-Prieto, 2019). Surprisingly, this focus has not extended to the realm influencer marketing, a field closely related to advertising studies.…”
Section: Introductionmentioning
confidence: 99%